Profil and Evaluation of Resistant Tuberculosis Drug’s Side Effect in Diabetes and Non Diabetes Mellitus Patient at RSUD Arifin Achmad - Dani Rosdiana; Dewi Anggraini; Indra Yovi; Marlina Tasril (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Backgrounds: Diabetes mellitus (DM) increases the risk of reactivation of tuberculosis included multi-resistant drug tuberculosis (MDR-TB). This situation is threatening Riau province due to the high prevalence of DM. Since 2014 Arifin Achmad Hospital as a referral hospital of MDR-TB management. It’s treatment especially in DM patients, requires an evaluation of both outcome and side effects. This evaluation needs to be compared with non-DM MDR TB patients. The aim of this study was to evaluate and analyse patient’s characteristic, conversion of smear or culture, drugs side effect and treatment outcome. Methods: This is a cross sectional retrospective study in RSUD Arifin Achmad Pekanbaru on April-October 2018. Sample of this study were all patients from 2014 – 2017. This study was divided into 2 groups, namely the DM and non-DM groups, then analysed the differences between the two groups Results: There were 113 MDR TB patients had its treatment, which 61% of the patients were male. Baseline data show 26.5% of MDR TB patients have comorbid DM. The most common side effects were nausea and vomiting (100%) in all subjects. In the MDR TB DM group, we found included: well controlled plasma glucose level was 33.3%, severe side effects was16.7%, conversion in the second month 40% and cured or complete treatment was 30%. Conclusions: As many as 26,5% of MDR TB patients had DM comorbidity. There were no differences in the percentage of drugs side effects, smear conversion in the second month and treatment outcome between MDR TB DM and MDR TB non-DM group. (J Respir Indo. 2020; 40(3): 156-62)